Interactions Between Genetic Risk and Diet Influencing Risk of Incident Female Gout: Discovery and Replication Analysis of Four Prospective Cohorts - Lin, Kehuan; McCormick, Natalie; Yokose, Chio; Joshi, Amit D.; Lu, Na; Curhan, Gary C.; Merriman, Tony R.; Saag, Kenneth G.; Ridker, Paul M.; Buring, Julie E.; Chasman, Daniel I.; Hu, Frank B.; et al. (Arthritis & rheumatology (Hoboken, N.J.), 2023)
Objective To examine whether the cross‐sectional gene–diet interaction for prevalent hyperuricemia among women translates prospectively to risk of incident female gout. Methods We analyzed the interaction between genetic predisposition and adherence to a healthy dietary pattern (i.e., Dietary Approaches to Stop Hypertension [DASH] score) on risk of incident female gout in 18,244 women from Nurses’ Health Study (NHS; discovery) and 136,786 women from 3 additional prospective female cohorts from the US and UK (replication). Genetic risk score (GRS) was calculated from 114 urate‐associated loci. Results In the NHS and replication cohorts, association between diet and gout risk was larger and stronger among women with higher genetic risk. In all cohorts combined, compared to women with an unhealthy DASH score (less than the mean score), multivariable relative risk (RR) for incident gout among women with a healthy DASH score (greater than/equal to the mean score) was 0.67 (95% confidence interval [95% CI] 0.60–0.76) among higher GRS (greater than/equal to the mean score) and 0.91 (0.78–1.05) among lower GRS (P for multiplicative interaction = 0.001); multivariable RR for higher versus lower GRS was 2.03 (95% CI 1.80–2.29) and 1.50 (95% CI 1.31–1.71) among unhealthy and healthy DASH score groups, respectively. Additive interaction was also significant, in both the discovery and replication cohorts (P < 0.001), with 51% of the excess risk attributable to the additive gene–diet interaction in all cohorts combined. Conclusion The deleterious effect of genetic predisposition on risk of incident female gout was more pronounced among women with unhealthy diets, with nearly half the excess risk attributable to this gene–diet interaction. These data elucidate the important synergy of genetics and diet for female gout development.